2021
DOI: 10.5070/p537151705
|View full text |Cite
|
Sign up to set email alerts
|

Justice in access to the outdoors

Abstract: Nature is an established social determinant of health with clear benefits to physical, mental, and social health, yet it continues to be used as a setting for violence against Black, Indigenous, and people of color (BIPOC). 1 The right to be physically active outdoors, to play, and to gather in community is essential for health and well-being, and as such, the ongoing incidents of violence outdoors have the potential to widen the health disparities gap. While the movement to bring nature and health together h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Research has shown that historically marginalized and socially vulnerable populations are more likely to experience the physical and mental health impacts of COVID-19 (Fortuna et al, 2020;Kim and Bostwick, 2020). Our evidence supports assertions that, within these communities, limited and diminishing use of park spaces during the pandemic could potentially widen health these disparities (Honey-Rosés et al, 2020;Taylor et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Research has shown that historically marginalized and socially vulnerable populations are more likely to experience the physical and mental health impacts of COVID-19 (Fortuna et al, 2020;Kim and Bostwick, 2020). Our evidence supports assertions that, within these communities, limited and diminishing use of park spaces during the pandemic could potentially widen health these disparities (Honey-Rosés et al, 2020;Taylor et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…While White participants were primarily concerned about hypodermic needles and strangers with mental health challenges, POC people talked about being afraid of violence and for their very lives while spending time in parks. This finding complements other research in adult populations indicating that public green spaces are perceived as a setting for violence for communities of color [23,57]. Fourth, we prioritized identifying solutions that would allow children to spend more time outside.…”
Section: Discussionsupporting
confidence: 60%
“…Pointedly, landscape-scale conservation relies on the public's continued support for parks as an idea-an idea favorable to the majority but falling short of fulfilling "in perpetuity" obligations to Black, Indigenous, People of Color (BIPOC) and members of the 2SLGBTQ+ community. All have reasons to be suspicious and fearful of the outdoors and parks (Byrne 2009;Taylor 2021;Davis and Edge 2022). Making parks welcome and safe spaces for everyone requires an exorcism of racism, intolerance, and bias in systems design, policy, and practice.…”
Section: All Things Are Connectedmentioning
confidence: 99%